Peningkatan Keterampilan Menulis Karangan Narasi Menggunakan Metode Quantum pada Siswa Kelas VII SMP Negeri 1 Malaka Barat - Anastasia Hoar Bria; E. Kristanti; Lenny Nofriyani Adam (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2022)
Abstract This study aims to obtain empirical data about learning to write narrative essays in class VII SMP Negeri 1 Malaka Barat with the Quantum learning method. Classroom action research went through two cycles which carried out using the cycle model of Stephen Kemmis. This research was conducted through four stages as follows: planning, implementation, observation and reflection. The results of the study stated that in the first cycle the average score was 61.31, 6 students who finished with a completeness percentage of 31.57% while students who did not complete as many as 13 students with a completeness percentage of 68.42%. While the average value of students in the second cycle is 92.36 of 19 students all completed with a percentage of completeness of 100%. The implications of the results of this study indicate that the application of the Quantum method is very effective and can improve learning achievement in writing narrative texts for students of SMP Negeri 1 Malaka Barat. Keywords: Writing skill, Narrative Essay, Quantum Method